Pharmacometrics and Systems Pharmacology Software Tutorials and Use: Comments and Guidelines for PSP Contributions. (18th December 2013) - Vicini, P; Friberg, LE; van der Graaf, PH; Rostami‐Hodjegan, A
Abstract : In addition to methodological Tutorials, 1 CPT:PSP has recently started to publish software Tutorials. 2, 3 Our readership and authors may be wondering what kind of format or product is expected, and the review of submissions we have already received prompted several discussions within the PSP Editorial Team. This editorial reflects on these discussions and summarizes their salient points. It aims at providing some details about the current vision of CPT:PSP for software tutorial articles. In addition, it brings some clarity on the topic of what role commercial software tutorials can have in CPT:PSP and how CPT:PSP tutorials differ from publications which describe the software itself, as those which can be found in other computer science journals. Finally, the discussion includes reproducibility considerations and the general use of commercial and noncommercial software in CPT:PSP publications. We hope our thoughts, and especially a stated requirement to publish user input to the software to aid in reproducibility, will help in guiding our authors and will stimulate healthy debate among our readers about the evolving nature of our science, how it can be facilitated using software and associated databases as a conduit, and what role this journal can play in fostering both the best modeling and simulation practices and the best scientific approaches to computational modeling, to bring the advantages of modeling and simulation to all regular practitioners, and not to just a (self) selected few. CPT Pharmacometrics Syst. Pharmacol . (2013) 2, e86; doi:10.1038/psp.2013.60 ; published online 18 December 2013